Efficacy of cryotherapy, hydrotherapy, and acupuncture on the health of competition horses: A systematic review (Research, Society and Development, 2025)
The maintenance of health in performance horses subjected to high training loads requires effective and safe recovery strategies. Therefore, the objective of this study was to evaluate the effectiveness of cryotherapy, hydrotherapy, and acupuncture in the recovery and performance of sport horses. A systematic literature review was conducted, following the PICO protocol, with searches performed in PubMed, SciELO, and the Virtual Health Library, resulting in the inclusion of 11 studies published between 2015 and 2025. The results show that cryotherapy is effective in controlling post-exercise pain and inflammation. Hydrotherapy promotes superior biomechanical adaptations, such as increased range of motion and muscle development, with protocols that can be customized according to water depth and speed. Acupuncture and pharmacopuncture stand out as non-doping modalities, significantly improving gait symmetry and reducing lameness. It is concluded that these three therapies are evidence-based interventions, whose integration into daily management contributes to optimizing performance, preventing injuries, and enhancing animal welfare, offering valuable alternatives for equine sports veterinary medicine.